Tantangan dan Peluang: Dinamika Keuangan Bisnis Mikro Dalam Budaya Patriarki UMKM Semarang - Suyati, Sri; Aminah, Siti; Khamimah, Khamimah; Supratiningrum, Supratiningrum (Jurnal Ilmiah Global Education, 2024)
This research aims to explore the influence of business characteristics and entrepreneur characteristics on the independence of formal debt decision making, by considering the moderating role of patriarchal culture. This study also aims to examine the impact of formal debt decision-making independence on business performance. The research was conducted through a survey of 248 female entrepreneurs in the food and beverage processing sector in Semarang. The research method uses descriptive and inferential analysis, with hypothesis testing carried out using Structural Equation Modeling Partial Least Square (PLS). The findings show that business characteristics and entrepreneur characteristics have a positive and significant influence on the independence of formal debt decision making. In addition, patriarchal culture is proven to play a moderating role, influencing the relationship between business characteristics/ entrepreneur characteristics and the independence of formal debt decision making. In other words, patriarchal culture modifies the influence of business characteristics and entrepreneur characteristics on formal debt decisions. The analysis also shows that independence in formal debt decision making has a positive impact on business performance. Thus, the results of this research imply the importance of independence in making formal debt decisions for female entrepreneurs in the food and beverage industry in Semarang.